1981
DOI: 10.1107/s0567740881005104
|View full text |Cite
|
Sign up to set email alerts
|

Transition-metal–crown-ether complexes. III. Seven-coordinate CoII in dinitratocobalt(II)–12-crown-4 and diaquacobalt(II) dinitrate–15-crown-5

Abstract: The structures of Con(NO3)2(12-crown-4), [Co(C s-H1604)(NOa)21, (I), and Con(H20)2(15-crown-5) -(NO3) 2, [Co(CIoH20Os)(H20)2I(NO3) 2, (II), have been determined from single-crystal X-ray diffractometer data at 291 (2) K and refined by least-squares methods to R = 2.7 and 4.7% respectively. The oxygen atoms of each crown-ether ring are directly coordinated to CC I, which is seven coordinate in each structure by additional coordination to two oxygens of one nitrate group and one oxygen of the other nitrate group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(11 citation statements)
references
References 10 publications
2
9
0
Order By: Relevance
“…In this way, the entire crystal lattice is ªgluedº together via these water/ crown interactions (Figure 1). A similar orientation has been observed with transition metal nitrates containing 12-crown-4 and 18-crown-6 as ligands and cocrystallised agents [4,5,27,28]. From our investigations, it has been found that the analogous europium complex is isostructural, adopting an identical non-threaded orientation with the coordinated water molecules participating in hydrogen bonding with the heteroatoms of the crown.…”
Section: Discussionsupporting
confidence: 57%
“…In this way, the entire crystal lattice is ªgluedº together via these water/ crown interactions (Figure 1). A similar orientation has been observed with transition metal nitrates containing 12-crown-4 and 18-crown-6 as ligands and cocrystallised agents [4,5,27,28]. From our investigations, it has been found that the analogous europium complex is isostructural, adopting an identical non-threaded orientation with the coordinated water molecules participating in hydrogen bonding with the heteroatoms of the crown.…”
Section: Discussionsupporting
confidence: 57%
“…As mentioned earlier, the smallest oxonium ion, H 3 O + , is approximately the same size as the cavity of 18C6 and therefore, based on size-fit arguments, there is little possibility of binding an H 3 O + ion within the cavity crown ethers such as 12C4 or 15C5. The effective diameter of the cavity of the larger of these, 15C5, 59 is approximately 0.9 A ˚smaller than that of 18C6, 60 and suggests that an H 3 O + ion will not fit in the interior of the crown. While the possibility of encapsulating an oxonium ion with 15C5 is all but eliminated, the crown can still act as a suitable hydrogen bond acceptor, setting up polymeric strands through successive oxonium ions and crown , the H 3 O + ion is bound between two 12C4 molecules as a discrete entity.…”
Section: Crown Ethers As Binding Agents For Oxonium Ionsmentioning
confidence: 97%
“…Fig. 20 X-Ray crystal structure of the polymeric chain in [H 5 O 2 + ][UO 2 (H 2 O) 2 Cl 3 ](15C5) 2 49,60. …”
mentioning
confidence: 99%
“…7, 8 Macrocyclic ligands and calixarene compounds are either too rigid or too flexible for complexation and instead result in the formation of uranyl salts or polymeric arrays with weak interactions. 9, 10 Schiff base (SB) ligands are potential candidates for selective separation as they contain multidentate mixed aza-and oxo-cores and possess sufficient steric freedom, while lacking the problems associated with macrocyclic cavity size. One drawback, however, is that Schiff base compounds are susceptible to hydrolysis and transamination by nucleophiles due to the presence of an imine group (C=N).…”
Section: Introductionmentioning
confidence: 99%